2018
DOI: 10.1002/star.201700320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microencapsulation on Antimicrobial and Antioxidant Activity of Nutmeg Oleoresin Using Mixtures of Gum Arabic, OSA, and Native Sorghum Starch

Abstract: Nutmeg (Myristica fragrans Houtt) and its solvent extracts are being used across the world for their strong anti‐inflammatory, antioxidant and antimicrobial activity attributed to their naturally occurring phytochemicals. The loading of nutmeg oleoresin in a matrix of gum arabic and sorghum starch (native and OSA modified) in different ratios is achieved in this study through microencapsulation by using a spray drying method. Morphological and chemical changes after modification of starch are analyzed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Their antimicrobial activity against food pathogens has been extensively reported [ 10 , 11 , 12 , 13 ]. Oleoresins (OR), in contrast, are viscous mixtures of essential oils and resins that are extracted from spices through organic solvents [ 14 , 15 ]. ORs can be found in liquid form when adding solvents such as propylene glycol, which also facilitates their use in food products [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their antimicrobial activity against food pathogens has been extensively reported [ 10 , 11 , 12 , 13 ]. Oleoresins (OR), in contrast, are viscous mixtures of essential oils and resins that are extracted from spices through organic solvents [ 14 , 15 ]. ORs can be found in liquid form when adding solvents such as propylene glycol, which also facilitates their use in food products [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of flour and bread extracts Control and composite flour and bread formulations (5, 10, 15 and 20) % were subjected to an extraction procedure stated by Arshad et al (2018). Dried samples (0.5 g) were extracted in 20 mL of 60% aqueous methanol (99.5% v/v), under continuous magnetic stirring at room temperature for 30 min followed by centrifugation at 2000 g for 10 min, and supernatant was collected for the analysis of total phenolic content and DPPH activity.…”
Section: Estimation Of Bioactive Componentsmentioning
confidence: 99%
“…It was found that compared with the original starch, the modified starch nano-microcapsules had excellent biological activity and functional properties. The results showed that the nano-microcapsules had excellent antioxidant activity and high retention rate of phenols and flavonoids after 60 d of storage, and exhibited resistance to Escherichia coli and Bacillus cereus ( 67 ). β-carotene (BC) and eugenol (EU) co-encapsulated flax seed oil (FSO) emulsions stabilized by octenyl succinic anhydride modified starches (OSA-MS) were dried to powders after the emulsification process.…”
Section: Preparation Of Starch-based Functional Food Nanomicrocapsule...mentioning
confidence: 99%